2010
DOI: 10.1007/s00216-009-3351-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of inclusions trapped inside Libyan desert glass by Raman microscopy

Abstract: Several specimens of Libyan Desert Glass (LDG), an enigmatic natural glass fromEgypt, were subjected to investigation by micro-Raman spectroscopy. The spectra of inclusions inside the LDG samples were successfully measured through the layers of glass and the mineral species were identified on this basis. The presence of cristobalite as typical for high-temperature melt products was confirmed, together with co-existing quartz. TiO 2 was determined in two polymorphic species, rutile and anatase. MicroRaman spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
5
13
0
Order By: Relevance
“…Residual Cretaceous-early Tertiary marine sediments are present in south-eastern Egypt (Hendriks et al, 1990) and the pluvial history and fluvial transport were documented in LDG, for example, by kaolinite, hematite and anatase coatings on individual sand grains (Fudali, 1981;Weeks et al, 1984). Fragments of anhydrite and aragonite enclosed within glass were also discovered in LDG (Swaenen et al, 2010), also supporting the proposed aqueous transport of the precursor sands. Eylers et al (1995) have experimentally confirmed that sand beds may effectively adsorb Li from stream water.…”
Section: Sources Of Tektites and Impact Glasses -The Evidence From LImentioning
confidence: 83%
See 1 more Smart Citation
“…Residual Cretaceous-early Tertiary marine sediments are present in south-eastern Egypt (Hendriks et al, 1990) and the pluvial history and fluvial transport were documented in LDG, for example, by kaolinite, hematite and anatase coatings on individual sand grains (Fudali, 1981;Weeks et al, 1984). Fragments of anhydrite and aragonite enclosed within glass were also discovered in LDG (Swaenen et al, 2010), also supporting the proposed aqueous transport of the precursor sands. Eylers et al (1995) have experimentally confirmed that sand beds may effectively adsorb Li from stream water.…”
Section: Sources Of Tektites and Impact Glasses -The Evidence From LImentioning
confidence: 83%
“…The particular feature of LDG is its extremely high silica content of >97 wt.% (Barnes and Underwood, 1976;Fudali, 1981). The presence of cristobalite in LDG (e.g., Swaenen et al, 2010) and the shock-metamorphic features in the proposed target area (Kleinmann et al, 2001) confirm an impact-related fusion origin (Frischat et al, 2001) from mature Cretaceous sandstones (or sands) derived from granites (Barrat et al, 1997;Pratesi et al, 2002;Schaaf and Mü ller-Sohnius, 2002), with a possible minor meteoritic component evident in slightly elevated platinum-group-element contents and Os isotope data (Murali et al, 1989;Barrat et al, 1997;Koeberl, 2000). Klitzsch et al (1979) and Fudali (1981) provided ample evidence for fluvial transport of parental material in the pre-impact history of LDG.…”
Section: Libyan Desert Glassmentioning
confidence: 99%
“…Apart from synthetic origin, fullerenes can be of natural origin from energetic events such as volcanic eruptions, flame generation or from biological algal remains [38][39][40]. In LDGs its presence was previously described [9].…”
Section: Libyan Desert Glass (Ldgs)mentioning
confidence: 99%
“…Nonetheless, they are also composed by other compounds, which are sometimes forming bubbles, black or brownish inclusions (possibly derived by melting or decomposition of iron oxides), dark or brown streaks and white cristobalite spherulites. The concentration of impurities is highly variable [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation